EXPRESSION OF COMMUNICATION SKILLS AND BENEFITS FOR CREATING AN EFFECTIVE MENTORING ENVIRONMENT. COMPARATIVE ANALYSIS OF THE CASE OF LITHUANIA AND LATVIA (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
This paper presents a comparative analysis of the survey results on communication competencies in mentoring in Lithuania and Latvia. In mentoring, it is imperative to examine barriers to communication competencies between business consultants (from now on referred to as "mentors") and start-up entrepreneurs or those intending to start a business (from now on referred to as "mentees") and propose solutions on how to enhance and maintain the business mentor network by utilizing communication technologies.